Structural health monitoring : current state and future trends - Pegoretti, Alessandro (Society of Automotive Engineers, 2018)
Sructural health management (SHM) is a key part of the integrated vehicle health management (IVHM) approach, whose main aim is to develop an integrated end-to-end system to monitor the overall health of a vehicle. It introduces the reader to recent developments involved in health monitoring of aerospace structures. The chapters, represented by seminal SAE International technical papers, offer an overview of the most recent advances in the sensing techniques for SHM, analysis of SHM data and its applications in aerospace.
Title from PDF title page (SAE Web site, 01/15/2019)
Keywords: Structural health monitoring.; Composite material -- Testing.; Structural analysis (Engineering); elektronické knihy; electronic books